Level of Retinol Deposit and Cervical Cancer - Tofan W Utami; Fera Ibrahim; Gatot Purwoto; Wely L Tiffani; Muhammad F Aziz; Andrijono Andrijono (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To analyze level of retinol deposit sufficiency in the natural history of cervical cancer. Methods: Serum retinol level was measured by ELISA from peripheral blood of subjects with normal cervix, cleared and persistent high risk human papilloma virus (HR-HPV) subclinical infection, and cervical cancer who fulfilled the inclusion and exclusion criteria. The study was held in Dr. Cipto Mangunkusumo and Fatmawati Hospital, Jakarta, within 2 years (August 2013- 2015). Blood was taken twice, consisting of post-8-hour fasting blood and 2 hours after 6000 IU retinyl palmitate oral administration. Results: Of 47 total samples, sufficient level of retinol deposit in normal cervix, cleared and persistent HR-HPV subclinical infection, and cervical cancer group was 85.0% (reference), 75.0% (OR 1.89), 33.3% (OR 11.33), and 75% (OR 1.89); respectively. Statistically, there was no significant difference from sufficiency level of retinol deposit between normal cervix and clearance HR-HPV subclinical infection (p=0.628), normal cervix and persistent HR-HPV subclinical infection (p=0.078), normal cervix and cervical cancer (p=0.433), cervical cancer and clearance HR-HPV subclinical infection (p=1.000), cervical cancer and persistent HR-HPV subclinical infection (p=0.430), persistent and clearance HR-HPV subclinical infection group (p=0.740). Conclusion: This study proves that normal cervix group has the highest level of retinol deposit sufficiency; however, it cannot be stated that cervical cancer group has less sufficiency level. Persistent HR-HPV subclinical infection group has the lowest level of retinol deposit (OR 11.33). There is no association between sufficient level of retinol deposit and clearance of HR-HPV. [Indones J Obstet Gynecol 2017; 5-1: 46-54] Keywords: cervical cancer, HR-HPV clearance, retinol deposit